PSICOLOGÍA RELIGIOSA Y FILOSÓFICA A FINAL DEL XIX E INICIOS DEL SIGLO XX - Tyutchenko, Alexander; Murashova, Olga; Fisenko, Olga (Revista Inclusiones, 2018)
In article the history of development of the Russian idealistic psychology is described religious and philosophical psychology.As subject of the analysis, the period of the end of XIX – beginning XX is chosen. At this particular time there is the Russian psychology which development was interrupted at first with world war of 1914, and then revolutionary events of 1917 and the civil war which followed it. During the Soviet period for the ideological reasons many representatives of religious and philosophical psychology were illegally forgotten, others were forced to emigrate from the country and further development of the Russian psychology was out of them. In article digression to history of development of psychology is given. It is proved that the Russian religious and philosophical psychology differs from European in the fact that it includes philosophical, theological and psychological knowledge. Its development is connected with search of spiritual identity of the nation.